DEVELOPMENT EXPERIENCE IN THE LAND OF PAPUA: A REVIEW OF THE APPLICATION OF THE DEVELOPMENT PARADIGM - Ohoiwutun, Yosephina (International Journal of Social Science, 2025)
This study aims to critically examine the dynamics of development in Papua by tracing the paradigm shift from centralization to regional autonomy and special autonomy. The main focus is to understand the extent to which the development approach that has been applied is able to address the issues of welfare and independence of the Papuan people. This research uses a descriptive qualitative method with a documentary study and content analysis approach. Data sources come from development policy documents, local government reports, and academic literature discussing development theory and practice in Papua. The research findings indicate that the dominant growth paradigm during the centralized era led to development disparities, marginalization of local communities, and weak community participation in the development process. The shift toward regional autonomy and special autonomy brought hopes for self-reliance, but faced challenges related to human resource capacity, local politics, and institutional limitations. A shift toward a community-based and socially just development paradigm is beginning to emerge, but it has not yet been fully realized. Therefore, the main recommendation of this study is the importance of strengthening local institutional capacity, consistently implementing participatory development mechanisms, and integrating local values into development planning to ensure the sustainability and relevance of policies at the grassroots level.